Source Credibility in the Community Service of Financial Literacy for Indonesian Vocational School Students - Salmiah, Neneng; Suci, Afred; Wiyati, Rita (UI Scholars Hub, 2023)
This paper examines the credibility of source persons for community service projects in improving financial literacy for vocational school students in Indonesia. Improving financial literacy among Indonesian youth is a long-term effort that requires multi- collaboration between the government, financial institutions, educational institutions, NGOs, and other stakeholders. Despite its substandard position to Singapore, Myanmar, and Malaysia, Indonesia’s financial literacy proficiency has improved significantly—one of which—after being catalyzed by the government’s cooperation with higher education institutions through community service programs. However, amid these improvements, greater attention must be given to capital markets, whose literacy level is most deficient compared to the banking, insurance, financing, pension fund, and financial technology sectors. By referring to the source credibility theory and PROSEM (problem rooting, solution treatments, and measurement) procedures, this study aims to improve vocational school students’ capital market literacy and determine the better expert (academician versus regulator experts) in providing basic capital market training to Indonesian vocational school students. Using 118 trainees, 59 each in classrooms trained by an academic and a capital market regulator separately, descriptive analysis along with ANOVA, paired- sample test, and independent samples test was used to observe the pre-and post-test of capital market literacy training. The results demonstrate significant improvement in students’ capital market literacy after the training. This study has demonstrated that credible trainers, especially those perceived as experts, are more effective as financial literacy sources for the trainees in capital market basic training. It provides a better guide for similar community services regarding selecting credible trainers or source persons.